Apoena: um jogo sério aplicado à saúde com foco em epidemiologia - BARATA, Bárbara Adriana Pires (2020)
Dengue is a negligible non-contagious vector-borne disease and several external factors contribute to its proliferation. One way to reduce the number of outbreaks of Dengue is to encourage population participation in actions to combat the disease. This work has developed a prototype of a mobile application based on an epidemiological system, using a serious game to disseminate environmental awareness in the fight against Dengue in public schools in Ananindeua, which has been living since 2013 in a state of emergency indicated by national basic sanitation rates. The game Apoena has its bases in agile methodology and uses in its construction the Construct 2 platform and Firebase as database. The game went through several stages in its development construction and it was necessary to develop a Short Game Design Document for Digital Educational Games (SGDDEdu) which is a document that seeks to describe the game in a more simplified and easy to understand. Internal tests in gameplay and mechanics were performed with the Alpha version to identify possible errors so that in the future the Beta version can be generated for testing with the target audience. Apoena offers a collaborative tool for collective health from its mechanisms helping the discussion in schools about epidemiological concepts and environmental awareness in a playful way.